Lung Cancer Subtypes Generate Unique Immune Responses - Busch, Stephanie E. (J Immunol, 2016)
Lung cancer – the leading cause of cancer-related deaths worldwide – is a heterogeneous disease comprised of multiple histologic subtypes that harbor disparate mutational profiles. Immune-based therapies have shown initial promise in the treatment of lung cancer patients but are currently limited by low overall response rates. We sought to determine whether the host immune response to lung cancer is predicated, at least in part, by histologic and genetic differences, as such correlations would have important clinical ramifications. Using mouse models of lung cancer, we show that small cell lung cancer (SCLC) and lung adenocarcinoma (ADCA) exhibit unique immune cell composition of the tumor microenvironment. The total amount of leukocyte content was markedly reduced in SCLC compared to lung ADCA, which was validated in human lung cancer specimens. We further identified key differences in immune cell content using three models of lung ADCA driven by mutations in Kras, Tp53, and Egfr. Although Egfr-mutant cancers displayed robust myeloid cell recruitment, they failed to mount a CD8(+) immune response. In contrast, Kras-mutant tumors displayed significant expansion of multiple immune cell types, including CD8(+) cells, regulatory T cells, IL17A-producing lymphocytes, and myeloid cells. A human tissue microarray annotated for KRAS and EGFR mutations validated the finding of reduced CD8(+) content in human lung adenocarcinoma. Taken together, these findings establish a strong foundational knowledge of the immune cell contexture of lung ADCA and SCLC and suggest that molecular and histological traits shape the host immune response to cancer.